2011
DOI: 10.21236/ada540725
|View full text |Cite
|
Sign up to set email alerts
|

A Complete System for Polyps Flagging in Virtual Colonoscopy

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In the case of colonography, CAD systems have shown high sensitivity and specificity for the detection of colonic polyps. 3, [12][13][14][15][16][17][18][19][20][21][22]35 It has been shown that the use of second-read CAD significantly improves polyp detection. 22 While CAD systems for colonography get increasing popularity and endorsement from the radiological community, they have not been designed to cope with the presence of stool, although labeling the stool with high contrast agents replaces the use of laxatives and reduces patient discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of colonography, CAD systems have shown high sensitivity and specificity for the detection of colonic polyps. 3, [12][13][14][15][16][17][18][19][20][21][22]35 It has been shown that the use of second-read CAD significantly improves polyp detection. 22 While CAD systems for colonography get increasing popularity and endorsement from the radiological community, they have not been designed to cope with the presence of stool, although labeling the stool with high contrast agents replaces the use of laxatives and reduces patient discomfort.…”
Section: Introductionmentioning
confidence: 99%